I wonder why the pyramids were built - "Steele, Philip" (Kingfisher London, 2011)
"I Wonder Why Pyramids Were Built: And Other Questions About Ancient Egypt" by Philip Steele. This children's book provides an engaging introduction to ancient Egypt, addressing questions about pharaohs, mummies, hieroglyphs, and more. The book is part of the "I Wonder Why" series, known for its lively question-and-answer format that combines realistic illustrations with engaging cartoons. This approach aims to both educate and entertain young readers, encouraging their curiosity about historical topics.